Keragaan Dua Varietas Jagung Hibrida Baru di Provinsi Kalimantan Timur - Pebriandi, Asep; Cahyana, Iyan; Sulhan, Sulhan (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
This study aims to determine the performance of new hybrid corn varieties JH 29 and JH 37 in East Kalimantan Province. This study was carried out in TPP Bangun Rejo, Bangun Rejo Village, Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan, from May to September 2022. The study consisted of two treatments, namely V1:  (JH 29) and  V2: (JH 37)—data analysis to compare between two new hybrid corn varieties treatments using a paired t-test. The results of the study showed variables that observed the location of the cob, the length of the cob, the number of rows/cobs, the weight of the cob, the weight of 1000 grains, and the results of the pile tons/ha did not show a real difference, while the height of the plant and the diameter of the cob showed a real difference from the two varieties of hybrid corn tested. The yield of hybrid corn varieties JH 29 is higher than verieties JH 37.